(untitled) (Annual of the Faculty of Philosophy in Skopje, 2014)
Work values are one of the most prominent parts in the personality structure. They have significant role in regulation of the person s behavior in different fields and in different situations, as well as in determination of the imopr tance of many life roles and the way of their accomplishment. In this paper few conceptions and typologies of work values are presented. It was emphasized that work values, through their crystallisation and hierarchical organization, are one of the key factors of occupational choice and person’s behavior in the workplace. Then, different approaches in explanation of their nature - preferences, i.e. goals (I like, It is important to me) and norms, i.e. stan dr ads (must/need) are discussed. In the final part of the paper empirical findings about their hierarchical structure are presented and compared.